The role of left fronto-parietal tracts in hand selection: Evidence from neurosurgery. (July 2020) - Howells, Henrietta; Puglisi, Guglielmo; Leonetti, Antonella; Vigano, Luca; Fornia, Luca; Simone, Luciano; Forkel, Stephanie J.; Rossi, Marco; Riva, Marco; Cerri, Gabriella; Bello, Lorenzo
Abstract: Strong right-hand preference on the population level is a uniquely human feature, although its neural basis is still not clearly defined. Recent behavioural and neuroimaging literature suggests that hand preference may be related to the orchestrated function and size of fronto-parietal white matter tracts bilaterally. Lesions to these tracts induced during tumour resection may provide an opportunity to test this hypothesis. In the present study, a cohort of seventeen neurosurgical patients with left hemisphere brain tumours were recruited to investigate whether resection of certain white matter tracts affects the choice of hand selected for the execution of a goal-directed task (assembly of jigsaw puzzles). Patients performed the puzzles, but also tests for basic motor ability, selective attention and visuo-constructional ability, preoperatively and one month after surgery. An atlas-based disconnectome analysis was conducted to evaluate whether resection of tracts was significantly associated with changes in hand selection. Diffusion tractography was also used to dissect fronto-parietal tracts (the superior longitudinal fasciculus) and the corticospinal tract. Results showed a shift in hand selection despite the absence of any motor or cognitive deficits, which was significantly associated with frontal and parietal resections rather than other lobes. In particular, the shift in hand selection was significantly associated with the resection of dorsal rather than ventral fronto-parietal white matter connections. Dorsal white matter pathways contribute bilaterally to control of goal-directed hand movements. We show that unilateral lesions, that may unbalance the cooperation of the two hemispheres, can alter the choice of hand selected to accomplish movements.